(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The purpose of this contribution is to examine the main issues concerning the clinical integration of genetic tests that use new sequencing techniques, known as Next-Generation Sequencing. The analysis focuses on the potential, the limits and the future challenges resulting from the wide availability of the new tests, given the recent decision of the U.S. Supreme Court in the case Association for Molecular Pathology v. Myriad Genetics.